2016
DOI: 10.18632/oncotarget.8008
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic effect of pregnancy on young female patients with nasopharyngeal carcinoma: results from a matched cohort analysis

Abstract: ObjectivesWe aimed to evaluate the prognosis of pregnancy-associated patients with nasopharyngeal carcinoma (NPC) in a young population.MethodsFrom June 1999 to December 2010, 51 patients aged ≤ 35 years who were diagnosed with NPC during pregnancy or within one year after delivery were admitted into the pregnancy-associated group in our institution. An additional 51 patients who were not pregnant at diagnosis were selected from 451 patients based on the matching criteria to match the pregnancy-associated fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Moreover, the result of the study is generally similar to previous studies, which indicated that childbirth itself may not negatively influence the survival outcomes in patients with pregnancy-associated NPC. 21,22 One woman, who wished to become pregnant after her NPC treatment, generally had a satisfying body recovery. The previous study about childbearing and survival after breast carcinoma in young women also has revealed that relatively healthier women are more likely to become pregnant than women with adverse disease sequelae or poor prognosis, 23 which is called "healthy mother effect" and it may account for the result that patients who had delivered a child had a better prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the result of the study is generally similar to previous studies, which indicated that childbirth itself may not negatively influence the survival outcomes in patients with pregnancy-associated NPC. 21,22 One woman, who wished to become pregnant after her NPC treatment, generally had a satisfying body recovery. The previous study about childbearing and survival after breast carcinoma in young women also has revealed that relatively healthier women are more likely to become pregnant than women with adverse disease sequelae or poor prognosis, 23 which is called "healthy mother effect" and it may account for the result that patients who had delivered a child had a better prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancy was associated with poorer prognosis, with one patient (11%) out of nine alive without disease at 5 years, compared with 83% in the nonpregnant group (P < .01). 35 in another case-control study of 102 patients. These results by Yan et al should be cautiously interpreted because 33% of their patients were in their eighth month of pregnancy, and radiotherapy was delayed until delivery.…”
Section: Diagnosis and Prognosismentioning
confidence: 97%
“…34 Similar results were reported. 35 in another case-control study of 102 patients. Both groups had 70% of advanced stages (P = .69).…”
Section: Diagnosis and Prognosismentioning
confidence: 97%